Food preference of nine-banded armadillo (Dasypus novemcinctus, Linnaeus, 1758) under human care - Pinke Testa, Carolyne Assis Eigenheer [UNESP]; Rosa, Patrícia Sammarco; de Castro, Thiago Ferla Novais; Sartori, Maria Márcia Pereira [UNESP]; Hippólito, Alicía Giolo [UNESP]; Silva, Maira Beatriz Gandolfi [UNESP]; Guimarães-Okamoto, Priscyla Tatiana Chalfun [UNESP]; Melchert, Alessandra [UNESP] (Springer Nature, 2022)
This study aims to evaluate the food preference of nine banded armadillos kept in captivity, exposed to four different diets: Diet 1 (D1) - dry dog food and ground beef; Diet 2 (D2) - dry dog food, ground beef, and chicken eggs; Diet 3 (D3) - dog food, ground beef, bananas, and papaya; Diet 4 (D4) - dog food, ground beef, chicken eggs, banana, and papaya. To this end, an experiment was carried out for five weeks, the first four of which were for preliminary management and the fifth week for data collection. Frequency of consumption, total intake for each diet, and intake ratio were evaluated. The dietary preference was higher for the diets with a higher protein percentage (D1 and D2), mainly D2, which presented increased demand and intake starting on the fourth day of observation. In second day of observation, D1 presented the higher intake ratio, but D2 gradually replaced it. The diet containing the lowest protein rate (D3) was the least favored on all observation days and evaluations. In conclusion, the food preference of ex-situ armadillos seems to be related to the inclusion of greater amounts of protein, particularly that of animal origin, with eggs being the most appreciated ingredient in this study.
Keywords: armadillo; Dietary adaptation; Dietary behavior; Food intake